The 5 love languages for men : tools for making a good relationship great / Gary Chapman with Randy Southern. - Chapman, Gary D.
Presents advice for men on how the five expressions of love--quality time, words of affirmation, gifts, acts of service, and physical touch--can be adapted to an individual marriage and used to enhance the quality of that relationship